(untitled) (SS Multidisciplinary Research Journal, 2024)
This article aims to investigate the marketing channels and supply chain dynamics in Onion production within Siraha District, Nepal. By analyzing the major marketing channels, the study seeks to identify the present status and constraints on both production and marketing processes. Through a combination of qualitative and quantitative research methods, including interviews with local farmers, traders, and stakeholders, as well as market surveys, this study had provided valuable insights into the challenges and opportunities facing onion producers and marketers in Siraha District. Most of the common marketing channel as “producers- local traders- wholesalers- retailers-consumers”. Onion traders in the study area were mostly facing the problem of storage as their major marketing constraint along with the fluctuating market price.